Coastal Vulnerability Assessment of Kanthi Coast, India by the Geospatial Technology - Dey, Nayan; Das, Payel (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
Since ancient times, most of the world’s civilization flourished along the banks of rivers and the coastal region. So the coastal region plays a vital role for human economic activities as well as their livelihood. The Kanthi coast, the northernmost part of the North Circus coast of India stretches in West Bengal and northern Odisha. The 45 km stretched coast land is associated with a dense population and faces the tropical cyclone emerging from the Bay of Bengal. The prime objective of the paper is to assess the coastal vulnerability of the study area. With the help of several indicators, viz. shoreline change rate, rate of sea level change, slope of the beach, wave height, tidal range, regional elevation, geomorphic features, sediment properties, coastal regulation zone (CRZ) violation ratio, the research work assess the Coastal Vulnerability Zone (CVZ) of the Kanthi Coastal region. The weightage sum method and Coastal Vulnerability Index (CVI) are being used. From this research work, it has been revealed that the western segment especially, Digha and Shankarpur are experiencing a high vulnerability situation.